Features of self-regulation of older adolescent students with different levels of reflection - Svetlana V. Veliyeva; Elena V. Zorina; Svetlana V. Yeshmeikina (Развитие образования)
The article examines the features of self-regulation of educational activity in senior adolescents depending on their level of reflexivity. At the first stage, reflexivity levels were determined in 257 students of grades 10–11 and 1–2-year medical college students using the reflexivity questionnaire by A.V. Karpov and V.V. Ponomareva and the differential reflexivity test by D.A. Leontiev and E.N. Osin. At the second stage, the features of self-regulation among adolescents with different levels of reflexivity were studied using the questionnaire "Style of Self-Regulation of Academic Activity – SSUD-M" by V.I. Morosanova. The results showed a predominance of the average level of reflexivity, a complete absence of a high level, and a significant proportion of adolescents with low reflexivity. Statistically significant differences in indicators of systemic reflection and introspection between groups with low and average reflexivity were revealed. Adolescents with an average reflexivity level demonstrated higher rates of planning, programming, evaluation of results, responsibility and independence in educational activities compared to peers with low reflexivity. The obtained data confirm the importance of reflection as a psychological mechanism contributing to successful self-regulation of educational activity and emphasize the need for targeted psychological and pedagogical work aimed at developing reflexive abilities of senior adolescents in the educational process.